Long non-coding RNAs PTENP1, GNG12-AS1, MAGI2-AS3 and MEG3 as tumor suppressors in breast cancer and their associations with clinicopathological parameters - Záveský, Luděk; Jandáková, Eva; Weinberger, Vít; Minář, Luboš; Kohoutová, Milada; Slanař, Ondřej (Disease markers. Section A, Cancer Biomarkers, 2024)
BACKGROUND: Breast cancer is the most commonly occurring cancer worldwide and is the main cause of death from cancer in women. Novel biomarkers are highly warranted for this disease. OBJECTIVE: Evaluation of novel long non-coding RNAs biomarkers for breast cancer. METHODS: The study comprised the analysis of the expression of 71 candidate lncRNAs via screening, six of which (four underexpressed, two overexpressed) were validated and analyzed by qPCR in tumor tissues associated with NST breast carcinomas, compared with the benign samples and with respect to their clinicopathological characteristics. RESULTS: The results indicated the tumor suppressor roles of PTENP1, GNG12-AS1, MEG3 and MAGI2-AS3. Low levels of both PTENP1 and GNG12-AS1 were associated with worsened progression-free and overall survival rates. The reduced expression of GNG12-AS1 was linked to the advanced stage. A higher grade was associated with the lower expression of PTENP1, GNG12-AS1 and MAGI2-AS3. Reduced levels of both MEG3 and PTENP1 were linked to Ki-67 positivity. The NRSN2-AS1 and UCA1 lncRNAs were overexpressed; higher levels of UCA1 were associated with multifocality. CONCLUSIONS: The results suggest that the investigated lncRNAs may play important roles in breast cancer and comprise a potential factor that should be further evaluated in clinical studies.
Keywords: tumor supresorové geny; regulace genové exprese u nádorů; Humans; lidé středního věku; RNA, Long Noncoding; RNA dlouhá nekódující; Biomarkers, Tumor; Genes, Tumor Suppressor; Female; Aged; dospělí; adaptorové proteiny signální transdukční; senioři; lidé; Adaptor Proteins, Signal Transducing; nádorové biomarkery; guanylátkinasy; Adult; Breast Neoplasms; Neoplasm Grading; ženské pohlaví; Middle Aged; prognóza; stupeň nádoru; nádory prsu; Guanylate Kinases; Gene Expression Regulation, Neoplastic; Prognosis